Green synthesis of silver nanoparticles using psychrotolerant strains of Tulasnella albida from South Orkney Islands (Antarctica) - Kobashigawa, Jesica María (2021)
Nanoparticles are widely studied due to their possible uses in biological and technological systems. Four psychrotolerant strains of Tulasnella albida isolated from Antarctica were tested and compared in their ability to synthesize silver nanoparticles. The four strains were capable of synthesizing silver nanoparticles with the addition of AgNO3 (final concentration of 0.5 mM), showing similar results under the same conditions: 28°C, 200 rpm, pH 9. Additionally, we registered the synthesis of nanoparticles at 6°C using biomass generated at the same temperature. For the characterization of synthesized nanoparticles, TEM and SEM microscopy analyses were performed. The images obtained showed the existence of spherically shaped silver nanoparticles with a log-normal size distribution centered at 2 nm diameter for 28°C. The largest ones showed a capping shell around them, appearing associated with the formation of small silver nanoparticles. Theoretical calculations of optical absorption based on core-shell Ag-Ag2O nanoparticles were used to characterize the experimental absorption spectra of silver nanoparticles colloids. This work contributes to expanding the studies and possible technological applications of psychrotolerant organisms in the industry, particularly in the green synthesis of nanoparticles at suboptimal conditions.